The Role of Swadesa Marketing Institutions in Increasing Farmers Income - Ar-Rozi, Ahmad Makky; Kolopaking, Lala M; Agusta, Ivanovich (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
One of The main problem faced by rice farmers is the marketing of agricultural products. To overcome these problems, Village Owned Enterprises (BUMDes) form a marketing agency, namely 'Swadesa' with on-line (e-commerce) and off-line (shop) systems. This study aims to analyze the role of Swadesa marketing institutions in improving the income of rice farmers. This research used qualitative and quantitative approaches (mix method). The research was conducted in Panggungharjo Village, Sewon District, Bantul Regency, Yogyakarta in March to October 2017. The results showed that this marketing agency could not run properly, so the purpose to increase farmer's income has not been achieved. Various obstacles that hinder the development of these marketing institutions, among others: lack of capital, lack of human resources (HR), low interest of farmers to sell crops, and digital iliteracy in rice farmers. Operational policies are needed in terms of increasing marketing agency access to capital sources; e-commerce utilization training; and more intensive socialization about the advantages of an on-line based marketing system.